Detection of Leishmania infantum in dogs (Canis familiaris) from São Paulo municipality, Brazil - Emiliano da Silva, Ryan (2020)
OBJETIVO: A leishmaniose visceral é causada por Leishmania infantum. No estado de São Paulo essa zoonose está em processo de expansão para áreas urbanas e a incidência da doença humana está relacionada com a infecção canina.  Neste trabalho, realizamos o diagnóstico sorológico e molecular em 152 cães (Canis familiaris) oriundos dos bairros Grajau e Ilha do Bororé, extremo sul do município de São Paulo, Brasil. MÉTODOS: Observamos a prevalência de L. infantum nesses animais, que são identificados como os principais reservatórios do agente etiológico da leishmaniose visceral. RESULTADOS: Os testes sorológicos mostraram baixo índice de positividade, enquanto os testes moleculares evidenciaram positividade em 3,94% e 0,65% para a catepsina L-like de Leishmania infantum e ITS do gene ribossomal, respectivamente. CONCLUSÃO: O diagnóstico molecular apontando para 3,94% de positividade, sugere a introdução de L. infantum nesta localidade de São Paulo, que ainda preserva 80% da Mata Atlântica. Nossos dados apontam para a necessidade de controle efetivo dos cães infectados para prevenir a disseminação da leishmaniose visceral em humanos. DESCRITORES: Leishmania infantum ,Cães, Sorologia, Diagnóstico molecular, São Paulo. Brasil. ABSTRACT OBJECTIVE: Visceral leishmaniasis is caused by Leishmania infantum. In the state of São Paulo, this zoonosis is expanding to urban areas and the incidence of human disease is related to canine infection. Herein, we performed a serological and molecular diagnosis on 152 dogs (Canis familiaris) from the Grajau and Ilha do Bororé neighborhoods, in the extreme south of the São Paulo municipality, Brazil. METHODS: We observe the prevalence of L. infantum in these animals that are identified as the main reservoirs of the etiologic agent of visceral leishmaniasis. RESULTS: Serological tests showed a low positivity rate, while the molecular tests showed positive animals at 3.94% and 0.65% for the Leishmania infantum L-like cathepsin and ITS of ribosomal gene, respectively. CONCLUSION: Molecular diagnosis of 3.94% positivity suggesting the introduction of L. infantum in this locality of São Paulo, which still preserves 80% of the Atlantic Forest. Our data point to the need for effective control of  infected dogs to prevent the spread of visceral leishmaniasis in humans.   DESCRIPTORS: Leishmania infantum,  Dogs, Serology, Molecular diagnosis, São Paulo, Brazil.